MRI hip findings in asymptomatic professional rugby players, ballet dancers, and age-matched controls. Issue 2 (February 2020) - Blankenstein, T.; Grainger, A.; Dube, B.; Evans, R.; Robinson, P.
Abstract : AIM: To investigate hip magnetic resonance imaging (MRI) findings in asymptomatic professional male rugby players and male ballet dancers compared to age-matched controls. MATERIALS AND METHODS: After ethics committee approval and consent from participants, 11 professional rugby players, 10 professional ballet dancers, and 10 controls completed activity and symptom questionnaires and underwent 3 T MRI of their self-declared dominant hip. Each scan was independently scored by two musculoskeletal radiologists for multiple features, including: joint morphology, acetabular labrum appearance, cartilage loss, and capsular thickness. Clinical and MRI features were assessed for variance by group using one-way analysis of variance (ANOVA) tests and Tukey post-hoc pairwise comparison of means. RESULTS: Labral tear prevalence was 87% with no significant difference between groups ( p> 0.05). Rates of paralabral cysts were significantly higher in ballet dancers (50%), compared to rugby players (0%) and controls (10%; p= 0.01). Acetabular cartilage loss was present in 54% with no significant differences between groups. Superior capsular thickness was significantly greater in ballet dancers (5.3 mm) compared to rugby players (3.8 mm) and controls (3.8 mm; p= 0.03). CONCLUSION: Despite the difference in type of activity between groups, there were equally high rates of labral tears and acetabular cartilage loss, questioning the role that sport plays in the development of these findings and their relationship to symptoms. The focally increased superior capsular thickness in ballet dancers may be an adaptive response to extreme ranges of movement. Highlights: High rates of labral tears in asymptomatic subjects. No difference in incidence despite different sporting and activity levels. Caution in interpreting labral tear and cartilage change as always being abnormal/symptomatic.